1993
DOI: 10.1038/clpt.1993.177
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 phenotype determines the metabolic conversion of hydrocodone to hydromorphone

Abstract: The contribution of cytochrome P450 2D6 (CYP2D6) to the formation of hydrocodone's active metabolite, hydromorphone, was examined in vitro and in vivo. Human liver microsomes prepared from an individual homozygous for the D6-B mutation of the CYP2D6 gene catalyzed this reaction at a negligible rate. Urinary metabolic ratios of hydrocodone/hydromorphone were highly correlated with O-demethylation ratios for dextromethorphan, an established marker drug of CYP2D6 activity (rs = 0.85; n = 18). The kinetics of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(91 citation statements)
references
References 2 publications
6
83
2
Order By: Relevance
“…A similar conclusion was drawn from studies on psychomotor effects and subject self-reporting of drug experience following oxycodone administration (Heiskanen et al, 1998). Studies examining O-demethylation of hydrocodone to hydromorphone have also shown that the parent compound appears to be responsible for analgesic effects in rats (Tomkins et al, 1997), monkeys (Lelas et al, 1999), and humans (Otton et al, 1993).…”
mentioning
confidence: 68%
“…A similar conclusion was drawn from studies on psychomotor effects and subject self-reporting of drug experience following oxycodone administration (Heiskanen et al, 1998). Studies examining O-demethylation of hydrocodone to hydromorphone have also shown that the parent compound appears to be responsible for analgesic effects in rats (Tomkins et al, 1997), monkeys (Lelas et al, 1999), and humans (Otton et al, 1993).…”
mentioning
confidence: 68%
“…The 2 -4 h duration of hydrocodone-induced analgesia [5] and the 3.8 -4.2 h hydrocodone half-life after ingestion of a single 10 mg dose [6,7] are compatible with brief duration of any post-ingestion inhibition of testosterone formation, supporting the possibility that this ingestion shortly before testosterone measurement might jeopardize its value in establishing a diagnosis of hypogonadism.…”
Section: Introductionmentioning
confidence: 74%
“…Other opioids. Production of the active metabolites of hydrocodone (hydromorphone) and oxycodone (oxymorphone) is reduced in CYP2D6 PMs (Otton et al, 1993;Heiskanen et al, 1998). However, there is little evidence of a difference in effect between EMs and PMs in human studies (Otton et al, 1993;Kaplan et al, 1997;Heiskanen et al, 1998) or in animal models (Tomkins et al, 1997;Lelas et al, 1999).…”
Section: Antipsychoticsmentioning
confidence: 99%